A human monoclonal antibody blocks malaria transmission and defines a highly conserved neutralizing epitope on gametes - Camila H. Coelho (Nature Portfolio, 2021)
Vaccines that interrupt malaria transmission will be important tools for malaria elimination. Here the authors identify a human monoclonal antibody from Pfs230 vaccinated individuals that blocks transmission of Plasmodium falciparum to mosquitoes in a complement-dependent manner and reacts with gamete surface.